1991
DOI: 10.1007/bf01250702
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with (18F)methylspiperone demonstrates D2 dopamine receptor binding differences of clozapine and haloperidol

Abstract: Four schizophrenic patients were investigated with dynamic positron emission tomography (PET) using (18F)fluorodeoxyglucose (FDG) and (18F)methylspiperone (MSP) as tracers. Two schizophrenics were on haloperidol therapy at the time of MSP PET. The other two schizophrenics were treated with clozapine, in one of them MSP PET was carried out twice with different daily doses (100 mg and 450 mg respectively). Neuroleptic serum levels were measured in all patients. Results were compared with MSP PET of two drug-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…This Figure shows that clozapine occupied low levels of D2 receptors, between 0 and 29%, when radiomethylspiperone congeners were used ([ 18 F]methylspiperone, 8 [ 11 C]methylspiperone 11,12 or [ 18 F]fluorethylspiperone 9,10 ), all of which have a dissociation constant of 0.092 nM (this lab, unpublished). 72 Clozapine occupied higher levels of D2 receptors, between 30% and 47%, [14][15][16][17][18][19] when [ 123 I]iodobenzamide was used with its higher dissociation constant of 0.43-0.49 nM.…”
Section: Therapeutic Levels Of Clozapine Occupy High Levels Of D2 Recmentioning
confidence: 99%
See 2 more Smart Citations
“…This Figure shows that clozapine occupied low levels of D2 receptors, between 0 and 29%, when radiomethylspiperone congeners were used ([ 18 F]methylspiperone, 8 [ 11 C]methylspiperone 11,12 or [ 18 F]fluorethylspiperone 9,10 ), all of which have a dissociation constant of 0.092 nM (this lab, unpublished). 72 Clozapine occupied higher levels of D2 receptors, between 30% and 47%, [14][15][16][17][18][19] when [ 123 I]iodobenzamide was used with its higher dissociation constant of 0.43-0.49 nM.…”
Section: Therapeutic Levels Of Clozapine Occupy High Levels Of D2 Recmentioning
confidence: 99%
“…It has been consistently claimed that clozapine only occupies between 0% and 50% of brain dopamine D2 receptors, as measured by a variety of radioligands using either positron tomography 1,2,[8][9][10][11][12][13] or single photon tomography. [14][15][16][17][18][19] This is in contrast to the D2 occupancies of 70 -80% for the typical neuroleptics.…”
Section: Therapeutic Levels Of Clozapine Occupy High Levels Of D2 Recmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not examine the effects of traditional neuroleptic treatment on amphetamine-induced raclopride binding to determine if classical antipsychotic agents and atypical drugs have differential striatal dopamine effects. Therapeutic doses of traditional antipsychotic agents show a steep dose-occupancy curve with apparent near-maximal binding of striatal D-2 receptors (i.e., у 80% estimated occupancy) (Farde et al 1988(Farde et al , 1992Wiesel et al 1990;Pilowsky et al 1993;Wolkin et al 1989;Coppens et al 1991;Karbe et al 1991) which could lead to baseline raclopride binding ratios that are too low to adequately assess amphetamine-related reductions in ligand binding. Another important issue is the lack of dopamine release data from A-10 dopamine neurons in limbic and cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the value of 10 nM for ritanserin at the D 2 receptor may account for the modest antipsychotic action of ritanserin (Meibach 1989;Duinkerke et al 1993;Heck et al 1994;Weisel et al 1994). Although Weisel et al found that doses of 10 to 30 mg of ritanserin did not affect the binding of [ 11 C]-raclopride to the D 2 receptors in three patients, ritanserin binds with low affinity (K of 10 nM) and would be expected to have a low occupancy of the D 2 receptors, similar to the situation with clozapine (Conley et al 1996;Farde et al 1992;Karbe et al 1991;Louerens et al 1993;Nordstrom et al 1996). Moreover, it also has been found that ritanserin, in contrast to clozapine, does not alleviate the extrapyramidal effects of haloperidol, but rather elicits a Drlike dystonia in haloperidol-sensitized primates (Casey 1991).…”
Section: Selective Antagonists For 5-htmentioning
confidence: 91%